The impact of financial development and market conditions on investment-cash flow sensitivity: global evidence - Ghani, Alan Nader Ackel (2016)
In this study, we analyze the impact of financial development and market conditions on investment-cash flow sensitivity during the 2006-2014 for 76 countries. First, the results show a relationship between investment-cash flow sensitivity and an index of financial development and its components. Second, 68 countries are affected by the 2008-2009 financial crisis, but only 16 countries exhibit a higher investment-cash flow sensitivity during the crisis. Third, investment-cash flow sensitivity is lower in countries with a larger primary debt market, while the size of the primary equity market has no impact. Finally, analyzing investment-cash flow sensitivity over time, we find lower sensitivity during years associated with higher primary debt market activity.